2004
DOI: 10.2214/ajr.182.2.1820447
|View full text |Cite
|
Sign up to set email alerts
|

Low Mechanical Index Contrast-Enhanced Sonographic Findings of Pyogenic Hepatic Abscesses

Abstract: Contrast-specific sonography was used to assess eight cases of aspiration-confirmed pyogenic liver abscesses. All cases were correlated with multiphasic helical CT findings. Continuous sonographic exploration allowed recognition of morphologic details not detectable on CT images. Contrast-specific sonograms showed features including rim enhancement, arteries along abscess margins and internal septa, dense and persistent septal enhancement, absent microcirculation in fluid and necrotic components, transient art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…A typical liver abscess is not difficult for diagnosis by contrast-enhanced sonography, and the enhancement features had been well depicted in previous series. 12,24 In this study, the lesion was 2.0 cm in diameter, and no liquefaction was found in the lesion, which appeared hyperenhancing during the arterial phase and hypoenhancing during the late phase. Therefore, it was difficult to differentiate it from other entities, especially HCC, without the information from clinical data.…”
Section: B a C Dmentioning
confidence: 52%
“…A typical liver abscess is not difficult for diagnosis by contrast-enhanced sonography, and the enhancement features had been well depicted in previous series. 12,24 In this study, the lesion was 2.0 cm in diameter, and no liquefaction was found in the lesion, which appeared hyperenhancing during the arterial phase and hypoenhancing during the late phase. Therefore, it was difficult to differentiate it from other entities, especially HCC, without the information from clinical data.…”
Section: B a C Dmentioning
confidence: 52%
“…Septa may also enhance after contrast agent administration and show a honeycomb-like appearance (Figure 8) [79] . A recent study of CEUS in infective liver lesions showed that most liver abscesses were irregularly rim-enhanced with non-enhanced central necrotic areas; whereas infect- …”
Section: Cystic Lesionsmentioning
confidence: 99%
“…A hypoechoic mass with irregular thick wall, with internal septa, sometimes containing gas (bright punctate echoes with dirty shadowing), are the most frequent ultrasound features of these lesions, but not specific. CEUS brings several typical elements that lead to a positive diagnosis, such as: marginal rim enhancement in the arterial phase, with enhancement of the septa (honeycomb appearance), with no enhancement in the liquid areas, and venous hypoenhancement [8][9][10].…”
Section: Introductionmentioning
confidence: 99%